Flat and ultra-broadband two-pump fiber optical parametric amplifiers based on photonic crystal fibers - Stefano Taccheo (Optical Review, 2018)
A two-pump fiber optical parametric amplifier (FOPA) based on the photonic crystal fiber (PCF) in the telecommunication region is investigated numerically. The fiber loss and pump depletion are considered. The influences of the fiber length, input signal power, input pump power, and the center pump wavelength on the gain bandwidth, flatness, and peak gain are discussed. The 6-wave model-based analysis of two-pump FOPA is also achieved and compared with that based on the 4-wave model; furthermore, the gain properties of the FOPA based on the 6-wave model are optimized and investigated. The comparison results show that the PCF-based two-pump FOPA achieves flatter and wider gain spectra with less fiber length and input pump power compared to the two-pump FOPA based on the normal highly nonlinear fiber, where the obtained results show the great potential of the FOPA for the optical communication system.